Biodiversity, gender and ethnicity. Biodiversidad, género y etnicidad - Howland, Fanny Cecile; Chavarro Rodriguez, Monica Juliana (2024)
The Gender Team at the Alliance Bioversity-CIAT (ABC) is leading two pivotal research studies: one focused on food waste and gender gaps in technology transfer, and another examining the role of a Colombian interethnic women's network in influencing policy and driving territorial changes related to climate change adaptation and biodiversity conservation. Funded by the CGIAR Gender Platform, both studies adopt an inclusive and differential approach. These research initiatives have highlighted persistent barriers to gender mainstreaming, such as training deficits, limited representation and participation in policymaking, and the lack of a gender and equity lens in research and policy processes. However, they have also underscored the significant strengths of local movements and ethnic communities, particularly in their relationship with nature. These communities harness traditional knowledge and innovative practices to foster equitable relationships among all living beings, yet they continue to face challenges of invisibility, gaps, and systemic barriers. In response, we have proposed an interethnic dialogue space to explore local alternatives and pathways for integrating science and politics with biodiversity conservation efforts. The goal of the proposed panel is to facilitate an interethnic and interdisciplinary dialogue, where Colombian women from diverse organizations and ethnic backgrounds can discuss gender and intersectionality in relation to biodiversity, public policy, and technology transfer. The panel is co-organized by ABC, the Natura Foundation (a Colombian NGO), and the Rural Women Directorate of the Colombian Ministry of Agriculture, and will feature leaders from indigenous, peasant, and Afro-Colombian community-based organizations actively engaged in biodiversity conservation.